1988
DOI: 10.1121/1.396874
|View full text |Cite
|
Sign up to set email alerts
|

Reference threshold sound-pressure levels for the TDH-50 and ER-3A earphones

Abstract: Reference threshold sound-pressure levels were established for a new insert earphone, the ER-3A tubephone, and for the TDH-50 earphone. In test-retest comparisons, the tubephone produced estimates of auditory threshold as reliable as the thresholds produced by the supraaural earphone. Reference thresholds were developed for the two earphones from data contributed by three laboratories. While the TDH-50 data are in good agreement with the provisional ANSI 6-cc coupler reference levels (ASHA, 1982), the ER-3A da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As the external auditory meatus is smaller and shorter in women than in men, it can be inferred that the residual space in the auditory meatus after the insertion of the sponge plug is also smaller in women, which would contribute toward a reduction in the amount of physiological noise in this space and would consequently enable obtaining lower thresholds. (9) This may explain the finding in the present study of significantly poorer thresholds with insert earphones among men when compared to the supra-aural earphones, whereas, for women, the results between transducers were similar or better with the insert earphones when compared to the supra-aural earphones.…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…As the external auditory meatus is smaller and shorter in women than in men, it can be inferred that the residual space in the auditory meatus after the insertion of the sponge plug is also smaller in women, which would contribute toward a reduction in the amount of physiological noise in this space and would consequently enable obtaining lower thresholds. (9) This may explain the finding in the present study of significantly poorer thresholds with insert earphones among men when compared to the supra-aural earphones, whereas, for women, the results between transducers were similar or better with the insert earphones when compared to the supra-aural earphones.…”
Section: Resultsmentioning
confidence: 39%
“…(4,5,6,7) However, a number of authors cite the disadvantages of insert earphones, such as the geometric variability of the external auditory meatus, insufficient dynamic range at high frequencies and problems related to hygiene with the use of sponge plugs. (1,8,9,10) The aim of the present study was to determine the influence of transducer type on the acquisition of hearing thresholds in individuals with severe neurosensory hearing impairment, comparing the responses between the use of TDH-39 supra-aural earphones and ER-3A insert earphones.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the use of insert earphones allows greater attenuation of external noise, reflected in lower auditory thresholds [8][9][10][11][12][21][22][23][24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
“…For use of the ER-3A insert earphones in equipment calibrated to the supra-aural and/or without automatic conversion headphones, the equipment manufacturer has recommended the use of correction factors to be added to the hearing threshold as described below 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed high test-retest consistency for the three transducers in both group of subjects. Another study reported test-retest data for 30 normal hearing adults using a standard clinical audiometer equipped with Telephonics TDH-50 supra-aural headphone and an Etymotic ER-3A insert earphone [20]. They concluded that insert ER-3A insert earphones produced estimates of auditory threshold similar to the TDH-50 earphone.…”
Section: Introductionmentioning
confidence: 96%